Zarządzanie kadrami w banku podczas przejęcia przez międzynarodową organizację finansową - Antczak, Zbigniew (HRM in a Polish bank. Results of scientific research, 2006)
The author presents the unique results of research, that prove the fact that the level of top managers qualifications highly influences the advancement of human resources management in a chosen banks in fusion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 155-164